Interface lift [user interface]. - Wohl, A.D.
This paper discusses the advent of new types of user interfaces that are designed not just for office workers but for a wide variety of users with special needs. While the interface for documents, folders and menus that is familiar to computer users today was a huge breakthrough compared with the command-driven interface that preceded it, it is by no means the most efficient way of handling information. Three interface categories are emerging. First is the browser interface, perhaps not the most efficient tool for a particular task, but with it users can move easily from one computer to another. Second is the special purpose interface for navigating large collections of information such as the Web. And finally, there are a variety of interfaces that computer users are beginning to acquire from both established and new companies for managing their own collections of information.
Keywords: Web; Browser interface; Information handling; Information management; Special purpose interface; User interfaces